Retail Companies' Value Determination Using Profitability As A Mediating Variable - Oktavia, Erni; Oktavia, Vicky; Subagyo, Herry; Prawitasari, Dian (Scimadly Publishing, 2025)
This study aims to examine the effect of liquidity and sales growth on firm value, with profitability as a mediating variable, in retail companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The analysis is based on secondary data derived from annual financial statements and IDX statistics. The research population consists of 51 retail sector companies, from which 95 observations were selected using purposive sampling based on specific criteria, covering 19 firms. The data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach with WarpPLS software. The findings reveal that liquidity has a significant positive impact on profitability, while sales growth does not significantly influence profitability. Furthermore, both liquidity and sales growth have a significant negative effect on firm value, whereas profitability positively and significantly contributes to firm value. However, the mediating role of profitability is not supported, as it does not significantly mediate the relationship between liquidity or sales growth and firm value. These results suggest that while improving liquidity can enhance profitability, it does not necessarily increase firm value. Additionally, sales growth alone is insufficient to improve either profitability or firm value without effective cost management. Profitability remains a critical determinant of firm value, highlighting the importance of operational efficiency and strategic financial management in the retail sector.